Methylation of the nonhomologous end joining repair pathway genes does not explain the increase of translocations with aging - Martin Guerrero, Idoia (2014)
Chromosome translocations are especially frequent in human lymphomas and leukemias but are insufficient to drive carcinogenesis. Indeed, several of the so-called tumor specific translocations have been detected in peripheral blood of healthy individuals, finding a higher frequency of some of them with aging. The inappropriate repair of DNA double strand breaks by the nonhomologous end joining (NHEJ) pathway is one of the reasons for a translocation to occur. Moreover, fidelity of this pathway has been shown to decline with age. Although the mechanism underlying this inefficacy is unknown, other repair pathways are inactivated by methylation with aging. In this study, we analyzed the implication of NHEJ genes methylation in the increase of translocations with the age. To this aim, we determined the relationship between translocations and aging in 565 Spanish healthy individuals and correlated these data with the methylation status of 11 NHEJ genes. We found higher frequency of BCL2-JH and BCR-ABL (major) translocations with aging. In addition, we detected that two NHEJ genes (LIG4 and XRCC6) presented age-dependent promoter methylation changes. However, we did not observe a correlation between the increase of translocations and methylation, indicating that other molecular mechanisms are involved in the loss of NHEJ fidelity with aging.